Would it be 2:1? I really don't know, I haven't learned that yet, sorry
Answer:
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3
Step-by-step explanation:
f(x) = x-1/3 and g(x) = 3x+1 what is (fog)(x)
f ( g(x) ) = (3x + 1) - (1/3) = 3x + 2/3
Or
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3
Answer:
the y intercept you are looking for is -3
Answer:
The first one : decay
The second one : growth
When the argument of the exponential expression is bigger that 1 then it represents a growth
When it's less than 1 and above 0 then it's a decay